Energy sensitive machining parameter optimisation. (6th May 2010) - Gupta, Deepak; Gopalakrishnan, Bhaskaran
Machining economics has been a challenging and interesting problem for decades. With the recent problems in supply of energy and increasing demand and cost, consideration of problems related to energy usage has become critical for the manufacturing industry. This paper aims to integrate the concept of machining economics and energy conservation. A geometric programming mathematical model was developed for the single pass turning operation. The model is based on an energy sensitive parameter selection process and minimises the overall cost of manufacturing. The solution methodology was developed to automate the process of parameters selection. Last but not the least; this paper is focused on increasing the energy efficiency awareness.